THE MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI MPLB PADA MATA PELAJARAN MANAJEMEN PERKANTORAN DI SMK - Putra, Muhammad Rendi Syah; Puspasari, Durinda (Jurnal Administrasi Pendidikan Indonesia, 2025)
Students' critical thinking skills in analyzing information, solving problems, and making decisions remain suboptimal. This study aims to analyze the Project-Based Learning (PjBL) model on the critical thinking skills of class XI students of Office Management and Business Services (MPLB) in the Office Management subject at SMK. This study uses an experimental method with a quasi-experimental nonequivalent control group design. The population in this study consisted of all class XI students at MPLB, with two classes selected as the experimental and control classes. Data collection techniques in this study used tests, interviews, observations, and documentation. The instrument used was a critical thinking test in essay form, consisting of 11 questions. Data analysis was carried out using normality tests, homogeneity tests, N-Gain tests, and independent-samples t-tests. The results of the study indicate that the Project-Based Learning model influences students' critical thinking skills in the office management subject at SMK. This is evidenced by the t-test results, which show a p-value of 0.000, which is less than 0.05. Therefore, the Project-Based Learning (PBL) model significantly improves the critical thinking skills of eleventh-grade students of Office Management and Business Services (MPLB) in the Office Management subject at vocational schools. The implications of this finding can be expanded by encouraging MPLB teachers to integrate PjBL into learning through projects relevant to the world of work.